OPTIMIZATION OF COMPLEX THERAPY IN PATIENTS WITH ARTERIAL HYPERTENSION АND THYROTOXIC CARDIOMYOPATHY - Schvets, N.I.; Bentsa, T.M.; Pastuchova, O.A.; Gdal, V.A.; Khairnasov, R.N.; Snisarevska, T.P. (World of Medicine and Biology, 2023)
The study included 69 patients with stage II arterial hypertension and moderate and severe thyrotoxicosis with thyrotoxic cardiomyopathy. All patients underwent general clinical, laboratory, and instrumental examinations followed by statistical processing of the obtained results. Patients were divided into control and main groups. Patients in the main group were prescribed quercetin in addition to basic and combined antihypertensive therapy. The results of this study prove that the additional use of quercetin has a reliable positive effect on the morpho-functional state of the heart by reducing the size and volume of the left atrium and ventricle, improving the systolic and diastolic function of the myocardium of the left ventricle and regression of hypertrophy with a decrease in the proportion of concentric hypertrophy. The patients also had a stable decrease in heart rate, a significant decrease in the number of extrasystoles, episodes of atrial fibrillation and their duration, an increase in temporal parameters of heart rate variability with normalization of the ratio of spectral indicators, compared to when using only basic therapy. Quercetin should be used as part of complex therapy for patients with arterial hypertension and thyrotoxicosis, with signs of thyrotoxic cardiomyopathy in order to minimize cardiovascular disorders, prevent the progression of structural and functional remodeling of the heart and the occurrence of arrhythmic complications.
Keywords: arterial hypertension; thyrotoxicosis; thyrotoxic cardiomyopathy; quercetin